The Ecuadorian paramo in danger: What we know and what might be learned from northern wetlands - Stefan Alexander Brück; Byron Daniel Medina Torres; Maria de Lourdes Teixeira de Moraes Polizeli (Global Ecology and Conservation, 2023)
The Paramo is a heterogeneous array of High Andean Mountain ecosystems above the tree line at elevations between 2800 and 5000 m. It unites characteristics of mountain ecosystems with those of wetlands, both of which are highly important in the context of global warming. It is considered the region with the highest global diversification rate on earth, capable of storing equally large amounts of soil organic carbon and vast quantities of water, forming wetlands within the paramo region, which are crucial for the sustainability of downslope Andean ecosystems and human settlements. These characteristics have attracted great scientific interest leading to an increase in publications, especially in the last decade. Nevertheless, the paramos diversity, difficult topology, latitudinal extension, location in developing countries, and the lack of historical data regarding the monitoring of soil characteristics, dynamics in hydrology, and climatic conditions still cause an important gap in knowledge necessary to estimate future climate change impacts, potential loss of ecosystem services and mitigation strategies. Substantial parts of its unique structure are seriously threatened to disappear before we discover all its secrets. Human intervention due to the upslope shift of agricultural activity, cattle farming, hunting, and wildfires have devastated large amounts of its landscapes. However, the biggest threat, global climate change, is still in its early phase of manifestation. In this context, the present review aims to summarize important characteristics of the Ecuadorian paramo with special emphasis on flooded and floodable areas, analyze what is known about principal threats and their future impact, and finally try to compare paramo research with northern wetlands to identify and discuss important knowledge gaps that remain to be filled.